2019
DOI: 10.23937/2469-5734/1510092
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Calcium Hydroxide Removal Activity of New Sonic System Vibringe and Different Irrigation Systems

Abstract: Vibringe® (Cavex Holland BV, Haarlem, Netherlands), which is marketed by a Dutch company as a sonic washing system, is a system in which manual and sonic activation are combined. It consists of an annular plunger compatible with a 10 ml Luer-lock syringe and a wireless and rechargeable battery. By pressing the button on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…[6][7][8][9] However, none of the irrigation techniques can provide complete removal of Ca(OH)2 remnants. 7,10,11,18 The aim of this study was to examine impact of various laser-assisted irrigation activation techniques on the removal of Ca(OH)2 from artificial grooves prepared in root canal walls. The results of the present study demonstrated that PIPS and Er:YAG laser groups were statistically more successful than needle irrigation and Nd:YAG laser groups (P < .05); no significant difference was determined between PIPS and Er:YAG laser groups (P> .05); no significant difference was determined between needle irrigation and Nd:YAG laser groups (P> .05) in regards to the removal of Ca(OH)2 remnants from apical grooves.The results for coronal grooves showed that no significant difference was determined among groups (P>.05).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] However, none of the irrigation techniques can provide complete removal of Ca(OH)2 remnants. 7,10,11,18 The aim of this study was to examine impact of various laser-assisted irrigation activation techniques on the removal of Ca(OH)2 from artificial grooves prepared in root canal walls. The results of the present study demonstrated that PIPS and Er:YAG laser groups were statistically more successful than needle irrigation and Nd:YAG laser groups (P < .05); no significant difference was determined between PIPS and Er:YAG laser groups (P> .05); no significant difference was determined between needle irrigation and Nd:YAG laser groups (P> .05) in regards to the removal of Ca(OH)2 remnants from apical grooves.The results for coronal grooves showed that no significant difference was determined among groups (P>.05).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous research [ 28 ], a power calculation was conducted by using the chi-square test family and variance statistical test (G*Power 3.1 software; Heinrich Hein University, Dusseldorf, Germany) with α = 0.05 and ß = 0.95, and the sample size was determined to be a minimum of 11 per group.…”
Section: Methodsmentioning
confidence: 99%
“…Ở nhóm bơm rửa kết hợp siêu âm, điểm số lượng calcium hydroxide còn lại ở 1/3 cổ, 1/3 giữa và 1/3 chóp khác biệt không có ý nghĩa thống kê (p > 0,05). Nghiên cứu của Aricioglu B và cộng sự (2019) cũng cho kết quả không có sự khác biệt về hiệu quả làm sạch calcium hydroxide giữa các phần ba chân răng khi bơm kết hợp với siêu âm [13]. Kết quả này có thể do khi kết hợp với siêu âm càng làm tăng hiệu quả bơm rửa vùng chóp của dung dịch.…”
Section: Bàn Luậnunclassified
“…Kết quả này có thể giải thích bởi hiện tượng "hiệu ứng khóa hơi". Trong trường hợp này, dòng chảy dung dịch bơm rửa không thể tiếp cận được vùng chóp của ống tủy, do không khí bị mắc kẹt giữa ống tủy và đầu kim bơm rửa dẫn đến rất khó để thực hiện quá trình làm sạch calcium hydroxide [13].…”
Section: Bàn Luậnunclassified